Small regulatory RNAs promoting the oxidative stress response and adaptive metabolic changes in Rhodobacter sphaeroides - Müller, Katrin Monika Hedwig; Justus Liebig University Giessen (My University, 2016)
The data obtained in the presented work again emphasise the importance of bacterial sRNA as regulators that fine-tune the metabolism and promote the stress defence upon changes in the environment (reviewed in Wagner and Romby, 2015). For the investigated model R. sphaeroides, a microorganism displaying a great metabolic versatility, many proteinaceous factors in the adaptation and response to environmental stimuli are known which mainly comprise receptors, transcription factors, and alternative sigma factors (described in 1.4, 1.6, 1.9.2, and 1.9.4). Since the discovery of a vast set of sRNAs in 2009 (Berghoff et al., 2009), the function of four of these sRNAs, namely PcrZ, CcsR1-4, SorY, and SorX, has been described (1.9.5), giving an even more detailed overview of the adaptation abilities of R. sphaeroides. In line with these descriptions, the here investigated sRNAs Pos19, PcrX, and RSs0827 affect adaptive metabolic changes as well as the cells response in the defence against oxidative stress. The sRNA Pos19 was found to affect pathways in the sulphur- and following glutathione (GSH) synthesis, by repressing a set of sulphur genes and the hypothetical protein RSP_0557. For the latter, a balanced expression seems to be required for a balanced cellular GSH pool. By means of these fine-tuning aspects of the sulphur metabolism that result in balanced cysteine and GSH levels, the RpoE-dependent sRNA Pos19 contributes to the refined response to oxidative stress. Additionally, Pos19 encodes a small peptide whose function so far remains enigmatic. Still, the survey concerning the peptide translation indicated that in R. sphaeroides the Shine-Dalgarno sequence is not essential for translation initiation, as it is known for other prokaryotes (Omotajo et al., 2015). The sRNA PcrX was found to be encoded in and processed from the 3 UTR of the puf mRNA. In the last years more and more focus was put on 3 UTR derived sRNAs (reviewed in Miyakoshi et al., 2015). Interestingly, PcrX was found to regulate its parental mRNA via binding to the pufX part of the polycistronic mRNA. The obtained data hint towards the hypothesis that PcrX is involved in the segmental stability of the puf mRNA which is needed to ensure the translation of the encoded photosynthetic components in a stoichiometric amount. Another facet of the sRNA besides the selfcontrol of its parental mRNA could be the regulation of additional genes. This idea is supported by the findings that the PcrX over-expression affects the mRNA levels of bchN and bchY, and that PcrX was found to be Hfq-bound, even though the effect on pufX seems to be independent of Hfq. Taken together, PcrX displays the second sRNA involved in the photosynthesis gene regulation of R. sphaeroides besides PcrZ. Regarding the sRNA RSs0827, the newly obtained data strongly support the finding that the sRNA interacts with and thereby regulates the rpoE mRNA. Therefore RSs0827 could display a potential regulator that ensures the attenuation of the RpoE-dependent stress response under certain conditions. So far an effect of RSs0827 on the RpoE-dependent sRNA Pos19 could only be found during the stationary phase, but not during conditions of photo-oxidative stress.

Die hier präsentierte Arbeit betont erneut die bereits häufig beschrieben Bedeutung von bakteriellen sRNAs als regulatorische Faktoren in der Stressantwort und der Adaption an Umwelteinflüsse (besprochen in Wagner and Romby, 2015). In dem betrachteten Modellorganismus R. sphaeroides sind in diesem Zusammenhang bisher vor allem Proteine mit regulatorischer Funktion bekannt. Diese umfassen Rezeptoren, Transkriptionsfaktoren, sowie alternative Sigma-Faktoren (beschrieben in 1.4, 1.6, 1.9.2 und 1.9.4). Seitdem im Jahr 2009 von Berghoff und Kollegen (Berghoff et al., 2009) eine Reihe von sRNAs in R. sphaeroides identifiziert wurden, konnte bereits für vier dieser sRNAs eine Funktion belegt werden (1.9.5). Darauf aufbauend konnten für die drei hier untersuchten sRNAs Pos19, PcrX, und RSs0827, Funktionen in der Regulation des Metabolismus und der oxidativen Stressantwort beschrieben werden. Die sRNA Pos19 beeinflusst den Schwefel- und den darauf folgenden Glutathion (GSH) Metabolismus indem sie reprimierend auf eine Reihe von Genen aus den entsprechenden Stoffwechselwegen, sowie auf das hypothetische Protein RSP_0557, wirkt. Für letzteres scheint eine genau definierte Expression die Voraussetzung für ein ausgeglichenes GSH Level zu sein. Durch den Einfluss auf den Schwefel-, Cystein- und GSH-Metabolismus trägt die RpoE-abhängig exprimierte sRNA Pos19 so zur ausbalancierten Antwort auf oxidativen Stress bei. Des Weiteren kodiert Pos19 ein kleines Peptid, dessen Funktion bisher noch unbekannt bleibt. Die Untersuchungen bezüglich des Peptids haben allerdings gezeigt, dass in R. sphaeroides die Shine-Dalgarno Sequenz für die Initiation der Translation nicht zwingend notwendig ist. Ähnliche Beobachtungen sind bereits für weitere Prokaryoten beschrieben (Omotajo et al., 2015). Die sRNA PcrX ist im 3 UTR der puf mRNA kodiert und wird aus der parentalen mRNA heraus prozessiert. In den letzten Jahren ist das Interesse an solchen in 3 - und 5 -UTRs kodierten sRNAs stetig gewachsen (besprochen in Miyakoshi et al., 2015). Bemerkenswerterweise deuten die gezeigten Daten darauf hin, dass PcrX den pufX Bereich der parentalen mRNA bindet und für die Prozessierung der puf mRNA eine Rolle spielt. Diese Prozessierung ist notwendig, um das stöchiometrische Verhältnis der durch die puf Gene kodierten Bestandteile des Photosyntheseappartes sicherzustellen. Neben dieser Selbstkontrolle , scheint die Regulation weiterer Gene durch PcrX möglich zu sein, da die Überexpression von PcrX neben pufX auch weitere Gene wie bchN und bchY stark beeinflusst. Und obwohl die Regulation von pufX durch PcrX Hfqunabhängig ist, wurde PcrX unter den sRNAs gefunden, die eine Bindung an Hfq aufgewiesen haben. Für die sRNA RSs0827 konnten die gewonnen Daten die bereits vermutete Interaktion mit der rpoE mRNA nachweisen. Durch diese Interaktion könnte RSs0827 die RpoE-induzierte Stressantwort unter ausgewählten Bedingungen abschwächen. Ein Effekt von RSs0827 auf die RpoEabhängige sRNA Pos19 wurde bisher aber lediglich in der stationären Phase gefunden.
Kleine regulatorische RNAs die die oxidative Stressantwort und die Adaption des Metabolismus in Rhodobacter sphaeroides unterstützen
Keywords: ddc:570